Effects of Dental Hygienists Job Stress on Somatization in an Area - Mi-Jeong Kim; Hyeon-Sun Kim; Cha-Young Lim (The Korean Society of Dental Hygiene Science, 2020)
Background: This study aims to analyze the job stress of dental hygienists and the factors affecting somatization and to provide basic data for effectively managing job stress and somatization of dental hygienists.Methods: In this study, the data collected from 208 dental hygienists working in Jeollabuk-do Province were analyzed. Job stress was investigated using a questionnaire with 43 questions. In addition, the degree of somatization was evaluated through a simplified psychotherapy examination (Symptom Check List-90-Revision).Results: Age, employment history, position, average monthly income, night duty execution status, and perceived health status were significantly associated with job stress (p＜0.05). The job stress sub-items scores based on general characteristics showed significance in 'workload' for those working a five-day workweek and perceived health status (p＜0.05). Age, average monthly income, and perceived health status were noted in 'role conflict as a professional'. In 'lack of expertise and skill', it was noted that age, employment history, position, income, and night clinic were implemented. In 'improper treatment and interpersonal issues', level of education and perceived health status were significant (p＜0.05). The higher the job stress, the higher the somatization symptom score (p＜0.05), and the higher the job stress component, the higher the somatization symptom score (p<0.01). Conclusion: The job stress of dental hygienists should be reduced, and the symptoms of somatization should be mitigated. To improve the quality of medical services and the work efficiency of dental hygienists, proper treatment and compensation systems should be implemented for them to take pride as professional. Further, programs and regulations on mitigating job stress and somatization symptoms should be developed.